Possible Relationship Between the Oral and Gut Microbiome, Caries Development, and Obesity in Children During the COVID-19 Pandemic - Reis, Ranam Moreira; Carlo, Hugo Lemes; Santos, Rogério Lacerda dos; Sabella, Fernanda Maria; Parisotto, Thaís Manzano; Carvalho, Fabíola Galbiatti de (Frontiers in Oral Health, 2022)
The COVID-19 pandemic has brought health damage and socioeconomic disruptions, together with lifestyle disorders around the world. Children are one of the most commonly affected, mainly due to social isolation and changes in eating habits and physical activities. This way, the risk of weight gain and obesity is possibly enhanced, as well as poor oral hygiene conditions and early childhood caries (ECC) development during the lockdown. In children under 6 years of age, ECC is defined as carious lesions in one or more primary teeth, with or without cavitation. Importantly, alterations in the oral microbiome caused by changes in children lifestyles have much more than a local impact on oral tissues, interplaying with the gut microbiome and influencing systemic environments. Recent studies have been exploring the oral health conditions, eating habits, and weight gain in the childhood population during the COVID-19 pandemic; however, there is a lack of information concerning the association among oral and gut microbiome, dental caries, and obesity in the COVID-19 era. In this context, this review aimed at analyzing a possible relationship between the oral and gut microbiome, caries, and obesity in children during the COVID-19 pandemic.